Palaeovegetation from a Homo neanderthalensis occupation in Western Liguria: archaeopalynology of Madonna dell'Arma (San Remo, Italy) - Kaniewski, D; Renault-Miskovsky, J; de Lumley, H (JOURNAL OF ARCHAEOLOGICAL SCIENCE, 2005)
This study presents a short local vegetation history of Western Liguria (San Remo), northwest Italy, based on a palynological analyses of an 8.30-m-long archaeological section in the dune covering Madonna dell'Arma cave. Madonna dell'Arma is one of the Mousterian caves currently located on the Ligurian coastal zone. The site contains Levallois-type Mousterian tools, four pieces of skull attributed to Homo neanderthalensis and fauna remains belonging to Rhinoceros mercki, Elephas sp. and Hippopotamus amphibius. This study is of interest as the site is situated in an area where data on palaeovegetation. are scarce. In fact, the archaeopollen analyses of Madonna dell'Arma cave's surroundings provide a rare local picture of vegetation during the beginning of OIS 4, posterior to 73,100 yr BP. The palynological taxa are grouped into three vegetation units by PCA (principal components analysis). These data suggest a huge Mediterranean pre-steppic forest (Pinus, Quercus ilex and several herbs) colonizing the area during this substage. The adjacent valleys were colonized by a caducifoliate-alluvial forest and Mediterranean scrub vegetation. These vegetation characteristics suggest a semi-arid coastal climate with an increase of precipitation according to altitude. The PCA analyses of the palynological sections inside and outside the cave suggest a nearly continuous vegetation succession from OIS 5a to OIS 4. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: archaeopalynology; Italy; Liguria; Middle Palaeolithic; OIS 4; PCA